2017
DOI: 10.1007/978-3-319-56535-4_89
|View full text |Cite
|
Sign up to set email alerts
|

Baby Steps in E-Health: Internet of Things in a Doctor’s Office

Abstract: IoT is a very common buzzword in e-Health because the creation of new and better healthcare services are possible through technology-push. There are great expectations in using IoT in healthcare, but most studies describe very futuristic and disruptive solutions for the healthcare real world. In a near future these solutions could be implemented, but now we need some "baby steps" to reach an e-Health with IoT technology. In this paper it is presented a solution to transform a doctor's office in an IoT office b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…For instance, concerning home healthcare, the solutions in [5,6] show IoT medical systems that were developed for home health monitoring. Finally, medical offices use intelligent systems to assist doctors in their daily tasks [7]. Numerous studies have demonstrated the importance of remote healthcare using IoT-based systems and the advantages it may offer in various situations.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, concerning home healthcare, the solutions in [5,6] show IoT medical systems that were developed for home health monitoring. Finally, medical offices use intelligent systems to assist doctors in their daily tasks [7]. Numerous studies have demonstrated the importance of remote healthcare using IoT-based systems and the advantages it may offer in various situations.…”
Section: Related Workmentioning
confidence: 99%